Development of the Financial System and Its Impact on Poverty Alleviation in Nepal - Acharya, Meena (NRB Economic Review, 2003)
The article reviews briefly the financial and monetary developments in Nepal since the mid-fifties both in developmental and poverty perspectives. Particularly, the role of the banking sector in rural financing and specific poverty targeted programs is reviewed in detail. Impact analysis is made on the basis of availability of data. The article concludes that, in spite of the tremendous growth of the financial sector in the post-liberalization period, its penetration in the rural areas has declined. There seem to be no backward or forward linkages of this financial development with the real sectors of the economy and, consequently, to poverty alleviation. Though government and non-government micro-financing institutions and also the cooperatives have grown fast in the 1990s, they are also concentrated in urban areas. The plethora of targeted credit programs has made very little dent in the rural credit market. More than 80 percent of the borrowing households have still to depend on non-formal sources for their credit needs. Majority of the targeted credit programs have been unable to directly cater to the needs of the bottom 20 percent households because the poor lack other resources and knowledge to benefit from the saving-credit programs. Lastly, inadequacy of financial and monetary data for evaluating the impact of financial development on the economy as well as on poverty is noted.